Instilling gender equality values as a formulation for preventing bullying behavior - Septi Wulandari; Esa Septian; Pradhana Hamdhallah Suryohayati; Fika Rizkia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Indonesia currently holds the 5th position globally in reported bullying cases, showing a prevalence rate of 41.10%. The pervasive nature of bullying within the education sector affects nearly every school in the country. This service activity is designed to tackle this issue head-on by highlighting the crucial role of gender awareness values in preventing bullying. The strategy involves a comprehensive approach, incorporating socialization sessions and focus group discussions, primarily targeting high school students. The intervention commences with informative sessions covering essential aspects like gender concepts, bullying education, and the interconnectedness of gender equality and bullying behavior. Subsequently, interactive discussions are facilitated through focus group discussions. The resulting positive outcomes indicate an enhanced understanding among students regarding gender-related learning and its pivotal role in preventing bullying. The service output includes actionable solutions, such as advocating for education on gender awareness, eliminating the culture of silence, strengthening gender-based school programs, encouraging cross-sector collaboration, and establishing an effective digital complaint platform to address bullying more efficiently.